A Bibliometric Analysis of The Term Cross-Cultural Marketing - Harti, Sugi; Rijal, Syamsu (International Journal of Business, Law, and Education, 2024)
This bibliometric analysis provides a comprehensive exploration of the scholarly landscape within cross-cultural marketing, offering insights into its historical evolution, predominant themes, and emerging trends. Through systematic data collection from reputable scholarly databases and rigorous analysis using VOSviewer, this study identifies influential literature and visualizes thematic clusters and trends. The findings underscore the dynamic nature of cross-cultural marketing, shaped by factors such as globalization, technological advancements, and cultural exchange. The implications of this research extend to academia and industry, emphasizing the importance of informed decision-making, collaborative efforts, and strategic interventions to maximize the potential of cross-cultural marketing for innovation, economic growth, and societal development.